Influence of neurotransmitter receptor variants on interactions with psychotropic drugs - Arranz, Maria (Henry Stewart Talks, 2007)
Pharmacological treatment in psychiatry, Causes of treatment variability, Genetic influence on drug-target interactions, Pharmacological profile of psychotropics, The dopaminergic system and drug response, Genetic influence on dopaminergic interactions, The dopaminergic system and drug response, Genetic influence on serotonergic interactions, Genetic variants and associations with treatment efficacy and side effects
Updated at 2014/12/02